BUSINESS AND PRODUCTION ECONOMIC DEVELOPMENT USING THE PATH ANALYSIS METHOD IN AQUACULTURE IN THE BONTOA SUB-DISTRICT, MAROS REGENCY - Anugriati Anugriati; Andi Ivo Asphama (International Conference on Social and Islamic Studies, 2021)
In the development of aquaculture, a study is needed to determine business and production economic development.  This research is expected to find out income level of traditional aquaculture business can find out the strategy development of aquaculture and can find out the economic model of business and production so that it can provide one of the information regarding development efforts  pond cultivation, the method used with path and swot analysis, the results of the research  This means that the income of traditional pond cultivation is 8,652,453.00 (Rp/MT), while total revenue of 10.392.769.00, the production which is significantly related is  income while Based on the SWOT analysis shows that the position of the development of traditional aquaculture business strategies is in the first quadrant (aggressive).  This strategy illustrates that traditional aquaculture businesses are in a position to be profitable, then the business can use the So strategy, namely business diversification of traditional pond cultivation by applying polyculture on pond cultivation land to  further increase production, given the high market demand for fishpond.